Assured destruction : building the ballistic missile culture of the U.S. Air Force - Bath, David W., 1966- (Transforming war, 2020)
"Assured Destruction: Building the Ballistic Missile Culture of the U.S. Air Force documents the rapid development of nuclear ballistic missiles in the United States and their equally swift demise after the Cuban Missile Crisis, revealing how these drastic changes negatively influenced both the Air Force and the missile community. The book contends that the creation of nuclear ballistic missiles threatened both the dominance of the United States during an intensifying Cold War and the strategic airpower mission of the newly created Air Force. The response to these threats led to political infighting and interservice squabbles to control the new weapon before the Soviets could build their own version and annihilate the United States. This highly politicized and hurried process prevented the successful long-term operational integration of ballistic missiles into the U.S. Air Force."--